Gombrowicz, Borges, and the Trap of a Cartographic Cosmos - Ubelaker Andrade, Max (Tropelías: Review of Literary Theory and Comparative Literature, 2024)
In his novel Cosmos (1965), Witold Gombrowicz describes the compulsive creation of an inassimilable cartography: an idiosyncratic ‘map’ that grows spontaneously from the narrator’s gaze, enveloping him in a shifting, unstable structure that subtly guides his actions. This essay argues that Gombrowicz, after over 20 years in Buenos Aires, writes Cosmos, in part, as a complex response to Jorge Luis Borges and his role as the foremost writer in Argentina. It proposes that Gombrowicz uses his novel to explore his ideas about the generative possibilities of cultural marginality in both Argentina and Poland while responding to one of Borges’s most famous stories: “Death and the Compass” (1942).